Characterisation Of Kenaf Fibre Reinforced Acrylonitrile Butadiene Styrene Composites For Fused Filament Fabrication - Mohd Farhan Han, Syaza Najwa (2021)
In this study, acrylonitrile butadiene styrene (ABS) polymer was reinforced with different percentages of kenaf fibres to produce fused filament fabrication (FFF) filaments. The degradation temperature, glass transition temperature (Tg), and melting temperature (Tm) of these newly developed filaments were evaluated via the thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The rheological properties of these filaments were also investigated based on viscosity and shear rate. Then, the FFF technology was used to produce three-dimensional (3-D) printed parts with kenaf fibre-reinforced ABS (K-ABS) polymer composites with different kenaf fibre fractions to investigate the mechanical behaviours of these parts. Tensile and flexural testings were performed on these 3-D printed samples. In general, the degradation temperature of K-ABS polymer composites decreased, as the content of kenaf fibre in K-ABS composites increased. Meanwhile, the Tg and Tm of samples increased when the content of kenaf fibre in K-ABS composites increased from 0% to 5%. However, the further increment of kenaf fibre content from 5% to 10% in K-ABS composite decreased the Tg and Tm of composites. For rheological properties, the viscosity decreased with increasing shear rate, but with no apparent difference observed the viscosities for K-ABS composites with different percentages of kenaf fibre. Tensile strength and tensile modulus of K-ABS polymer composites decreased by 50.5% and 43.8% for K-ABS composites with kenaf content of 0% and 5%, respectively. The increasing content of kenaf fibre from 5% to 10% in K-ABS composites increased the tensile strength by 61.9% and tensile modulus by 49.4%. Flexural strength and flexural modulus decreased by 34.7% and 46.9% in K-ABS composites with kenaf fibre of 0% and 5%, respectively. Further addition of kenaf fibre in K-ABS from 5% to 10% increased the flexural strength and flexural modulus by 23.3% and 47.4%, respectively. The presence of porosity and poor interfacial adhesion between kenaf fibre and ABS matrix, as revealed in failure mode, may have caused the decrease of mechanical properties. Overall, K-ABS composite with 2.5% kenaf fibre was the best materials with better performance in the testing of thermal, rheological and mechanical properties and failure mode analysis. This research successfully demonstrated the capability of K-ABS composites with different kenaf fibre content serving as FFF filaments.